2001
DOI: 10.1089/08892220150503681
|View full text |Cite
|
Sign up to set email alerts
|

Membrane-Perturbing Domains of HIV Type 1 Glycoprotein 41

Abstract: Structural and functional studies were performed to assess the membrane actions of peptides based on HIV-1 glycoprotein 41,000 (gp41). Previous site-directed mutagenesis of gp41 has shown that amino acid changes in either the N-terminal fusion or N-leucine zipper region depressed viral infection and syncytium formation, while modifications in the C-leucine zipper domain both increased and decreased HIV fusion. Here, synthetic peptides were prepared corresponding to the N-terminal fusion region (FP-I; gp41 resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
14
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 91 publications
5
14
0
Order By: Relevance
“…This effect was more pronounced for the 208 nm band in simple proteoliposome preparations. The shift of the positive band, together with the Ө 222 /Ө 208 ellipticity ratio >1, would support the existence of helix-helix interactions such as those described for heterodimeric coiled-coils48495051 and/or transmembrane helical bundles52. Seemingly, the protein in solution shows a Ө 222 /Ө 208 ellipticity ratio <1, which would be consistent with the disruption of helix-helix interactions or monomeric alpha-helix50.…”
Section: Resultssupporting
confidence: 59%
“…This effect was more pronounced for the 208 nm band in simple proteoliposome preparations. The shift of the positive band, together with the Ө 222 /Ө 208 ellipticity ratio >1, would support the existence of helix-helix interactions such as those described for heterodimeric coiled-coils48495051 and/or transmembrane helical bundles52. Seemingly, the protein in solution shows a Ө 222 /Ө 208 ellipticity ratio <1, which would be consistent with the disruption of helix-helix interactions or monomeric alpha-helix50.…”
Section: Resultssupporting
confidence: 59%
“…However, T20 and other gp41 targeting peptides have also been found to display antihemolytic activity [17,35]. Assays evaluating synthetic peptide-peptide gp41 may not truly mimic the complex interaction of gp41 in its natural conformations.…”
Section: Discussionmentioning
confidence: 99%
“…Extension of FP to include partial sequence of NHR region results in significant enhancement of FP-mediated membrane fusion, suggesting that NHR has a synergistic role in FP-mediated fusogenic activity (57). Mobley et al (58) demonstrated that T-20 can block hemolysis and cell aggregation induced by FP and the N-peptide fusion inhibitor T-21, implying the interaction of T-20 with the FP. It is plausible that T-20 inhibits the viral fusion by affecting the membrane perturbations associated with the interactions of FP and NHR, which underlie the merging of the viral envelope with the target cell membrane.…”
Section: T-20 Targets Multiple Sites In Gp120/gp41mentioning
confidence: 99%